2021
DOI: 10.1016/j.shaw.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

How Effectively Safety Incentives Work? A Randomized Experimental Investigation

Abstract: Background Incentive and penalty (I/P) programs are commonly used to increase employees' safety outcomes, but its influence on employees' safety outcomes is under-investigated. Moreover, under developed economies lack safety culture and there is dearth of literature focusing on empirical studies over there [1]. Based on these gaps, this study attempts to see the impact of I/P programs on safety outcomes in a developing country. Methods The study was carried out in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Consequently, the staff makes no positive changes ( 45 ) . On the other hand, a randomized experimental study found that incentives impact motivation for safety reporting but are not used over the long term because salary increases to improve safety culture have a short-term impact ( 49 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the staff makes no positive changes ( 45 ) . On the other hand, a randomized experimental study found that incentives impact motivation for safety reporting but are not used over the long term because salary increases to improve safety culture have a short-term impact ( 49 ) .…”
Section: Discussionmentioning
confidence: 99%
“…An easier tactic might be to introduce a safety employee of the month as an ego boost because this is generally better than nagging where an operative will shut off (Leathley, 2016). Offering time in lieu of an extra day holiday for coming up with good safety incentives or consistent, safe behaviour was considered a commendable reward and was reiterated by Ahmed and Faheem (2021) that incentive and penalty (I/P) programs are commonly used to increase employees' safety good behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In a safety culture, people are rewarded for improving safety, either as individuals or team members. A study conducted by Ahmed and Faheem (2021) showed that incentives affect motivation to carry out safety reporting but are not applied in the long term because salary to improve safety culture is only effective in the short term. The organization needs to establish an appropriate approach to enhance the continuous reporting of safety incidents over a long period.…”
Section: Support For Nursesmentioning
confidence: 99%